DETERMINATION OF NURSES’ KNOWLEDGE IN INITIAL HANDLING OF EMERGENCY PATIENTS IN THE CRITICAL UNIT OF SUMBAWA REGIONAL GENERAL HOSPITAL - Ismaildin Ismaildin; Risha Setyowati (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Rapid and accurate initial management of emergency patients is crucial to prevent mortality and disability, especially in critical care units. However, variations in nurses’ knowledge and preparedness—often influenced by education, experience, and training—highlight the need to assess factors affecting their competence in emergency management. Objectives: This study aimed to assess nurses’ knowledge of initial emergency management and identify factors associated with their knowledge levels in the critical care units of Sumbawa Regional General Hospital. Methods: Analytical descriptive (cross-sectional) quantitative study conducted in June 2025. The target population comprised nurses working in the Emergency Room, ICU, NICU, and Surgical unit (N = 60). A total of 52 nurses participated (response rate 86.7%) and were included using convenience (accidental) sampling. Data were collected using a structured questionnaire assessing knowledge of initial emergency management. Knowledge was categorized as Good (≥75%), Sufficient (50–74%), and Lacking (<50%) based on the total score. Analysis included descriptive statistics and bivariate analysis using the Chi-square test (α = 0.05). Results: Of 52 respondents, 44.2% (n = 23) demonstrated Good knowledge, 25.0% (n = 13) Sufficient knowledge, and 30.8% (n = 16) lacked knowledge. Bivariate analysis showed significant associations between knowledge level and educational level (p = 0.041), length of work (p = 0.035), and previous emergency training (p < 0.001). Conclusion: Knowledge of initial emergency management among nurses at Sumbawa General Hospital is heterogeneous, with gaps associated with lower formal education, shorter work experience, and lack of training. We recommend regular, simulation-based, and blended BLS/PPGD training, periodic competence assessments, and hospital-level policies to ensure mandatory life-support certification for critical care nurses.